Analysis of Physics E-LKPD Needs Based on Problem-Based Learning to Improve Students’ Critical Thinking Skills - Usparianti L, Yurika; Marlina, Leni; Wiyono, Ketang (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2023)
The development of ICT and 21st-century learning emphasizes improving students' critical thinking skills. So that the learning process requires teaching materials that can attract students' interest and motivation to learn. This study aims to analyze the need for physics teaching materials for teachers and students at SMP Sriguna Palembang. The teaching material to be developed is an electronic LKPD (E-LKPD) in learning Physics using a quantitative approach with the survey method. The instrument used was a questionnaire containing the needs of E-LKPD teaching materials for teachers and students at SMP Sriguna Palembang, which were distributed via Google Forms. Respondents involved in this study were four teachers and 33 students using a simple random sampling technique. The data obtained were analyzed descriptively in the form of percentages. The results showed that the teachers and students of Sriguna Palembang Middle School needed interactive teaching materials in the form of Problem-Based Learning-based E-LKPD to learn Physics material.